Survival Benefit of Pyloric Lymph Node Dissection for Siewert Type II/III Adenocarcinoma of the Esophagogastric Junction Based on Tumor Diameter: A Large Cohort Study - Lin, Xia; Li, Zhengyan; Tan, Chenjun; Ye, Xiaoshuang; Xiong, Jie; Liu, Jiajia; Mo, Ao; Shi, Yan; Qian, Feng; Yu, Peiwu; Zhao, Yongliang (Frontiers in Oncology, 2021)
Background It is unclear whether the dissection of pyloric lymph nodes (PLNs, No. 5 and No. 6 lymph nodes) is necessary for adenocarcinoma of the esophagogastric junction (AEG) with a tumor diameter >4 cm based on current guidelines. This study aimed at evaluating whether pyloric node lymphadenectomy is essential for patients with Siewert type II/III AEG according to different tumor diameters. Methods This study included 300 patients on whom transabdominal total gastrectomy was performed for Siewert type II/III AEG at a high-volume center in China from January 2006 to December 2015. The index of estimated benefit from lymph node dissection (IEBLD) was used to analyze the priority of pyloric lymphadenectomy. Results In Siewert type II AEG, the 5-year overall survival (OS) and the 5-year disease-free survival (DFS) were similar between patients with PLN-positive cancer and patients of stage III AEG without PLN metastasis (23.1% vs. 30.6%, p = 0.505; 23.1% vs. 27.1%, p = 0.678). However, in Siewert type III AEG, the OS and the DFS of patients with PLN-positive cancer were significantly lower than that of patients with stage III without PLN metastasis (7.9% vs. 27.8%, p = 0.021; 0 vs. 26.8%, p = 0.005). According to the IEBLD, the dissection of PLNs did not appear to be beneficial in either Siewert type II AEG or type III AEG, whereas a stratified analysis revealed that PLN dissection yielded a high therapeutic benefit for Siewert type II AEG with tumor diameters >4 cm. Conclusion We recommended that the PLNs be dissected in Siewert type II AEG when a tumor diameter is >4 cm. Total gastrectomy should be optional for Siewert type II AEG with a tumor diameter >4 cm and Siewert type III AEG.